2000
DOI: 10.1536/jhj.41.425
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte-depleted Continuous Blood Cardioplegia for Coronary Artery Bypass Grafting

Abstract: SUMMARYMany cardiac surgeries are performed with blood cardioplegia. However, some studies suggest that activated neutrophils form blood cardioplegia can cause reperfusion injury. In this study we assessed myocardial protection using a leukocyte-depleted cardioplegic solution.Patients undergoing elective coronary artery bypass grafting (CABG) with continuous blood cardioplegia were divided into two groups: the LD group, which received leukocyte-depleted blood cardioplegia (n = 11); and the control group, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…vs (2) have demonstrated a significantly lower maximum dose of inotrope at weaning of CPB in the leukodepleted group, but in their later study could only replicate this in patients who had extended aortic cross clamp time [73]. Other investigators, who predominantly studied uncomplicated elective cases, found no significant difference in any post-operative haemodynamic parameter [70,71,76,78,81].…”
Section: Cardiac Function Palatianos Et Al In a Largementioning
confidence: 94%
See 1 more Smart Citation
“…vs (2) have demonstrated a significantly lower maximum dose of inotrope at weaning of CPB in the leukodepleted group, but in their later study could only replicate this in patients who had extended aortic cross clamp time [73]. Other investigators, who predominantly studied uncomplicated elective cases, found no significant difference in any post-operative haemodynamic parameter [70,71,76,78,81].…”
Section: Cardiac Function Palatianos Et Al In a Largementioning
confidence: 94%
“…These papers are summarised in Table 2. Fourteen were randomised control trials, and in one case the study design is not clear [70].…”
Section: Part B: Leukocyte Filtration Of the Cardioplegia Linementioning
confidence: 99%
“…28 Leukocyte-depleted blood cardioplegia in humans produced lower levels of CK-MB and troponin T in blood obtained from the coronary sinus after unclamping of the aorta, in comparison to patients receiving non-leukocyte-depleted cardioplegia. 29,30 Enzyme plasma levels were similar in both groups after completion of the operation. 29…”
Section: Cardioplegic Leukocyte Filtration: Effects On Inflammatory Mmentioning
confidence: 74%
“…Q Chen a , S Shepard a , V Clinton b a Southampton University Hospital, Tremona Road, Southampton, Hants, UK; b DeMontfont University, The Gateway, Leicester, LE1 9BH, UK The removal of leukocytes from blood cardioplegia during cardiopulmonary bypass (CPB) has been demonstrated to improve myocardial protection during cardiac surgery. 1,2 This study was conducted to evaluate the filtration mechanism of the blood cardioplegia filter media (BC1B Pall Biomedical, Portsmouth, UK).…”
Section: Removal Of Activated Neutrophils During Blood Cardioplegia Fmentioning
confidence: 99%